2021
DOI: 10.3389/fpubh.2021.694368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Malnutrition Assessment Scales in Predicting Postoperative Complications in Elderly Patients Undergoing Noncardiac Surgery

Abstract: Background: The present study was designed to investigate the relationship between two malnutrition assessment scales, perioperative nutrition screen (PONS) and Nutritional Risk Screening 2002 (NRS2002), with postoperative complications in elderly patients after noncardiac surgery.Methods: This was a secondary analysis of a prospective cohort study. Elderly patients (65–90 years) undergoing noncardiac surgery were enrolled in Peking University First Hospital. Malnutrition was screened by PONS and NRS2002 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The NRS2002 scale is commonly used to assess patients' nutritional status comprehensively. Previous results have shown that the NRS2002 score is associated with postoperative complications in patients [ 37 , 38 ]. Patients with poor preoperative nutritional status are at increased risk of postoperative anastomotic leakage, which may be due to the prolonged healing time of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The NRS2002 scale is commonly used to assess patients' nutritional status comprehensively. Previous results have shown that the NRS2002 score is associated with postoperative complications in patients [ 37 , 38 ]. Patients with poor preoperative nutritional status are at increased risk of postoperative anastomotic leakage, which may be due to the prolonged healing time of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a systematic review with the same tool showed that malnutrition patients are more at risk for mortality than the patients with normal nutrition and have a lower quality of life (35). Patients with more malnutrition than patients with normal nutrition are at risk for complications and manifestations after surgery, such as wound infection and recurrent pain (36). Also, the results of other studies show that there is a significant relationship between energy intake in patients hospitalized in ICUs and infection (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size estimation was based on the post‐operative morbidity and on the principle of 10 outcome events per variable. Referring to previous literatures, the morbidity in elderly patients was about 38% 24 . Using an estimated morbidity of 38% and for 20 predictors, we aimed to enrol 526 patients.…”
Section: Methodsmentioning
confidence: 99%